Cost‐Effectiveness of a Weight Loss Intervention: An Adaptation of the Look AHEAD Lifestyle Intervention in the US Military. Issue 1 (26th November 2019) - Manz, Karina C.; Waters, Teresa M.; Clifton, Hannah E.; Kocak, Mehmet; Klesges, Robert C.; Talcott, G. Wayne; Krukowski, Rebecca A.
Abstract : Objective: This study aimed to assess whether a counselor‐initiated (CI) adaptation of the Look AHEAD (Action for Health in Diabetes) intensive lifestyle intervention in a military setting was cost‐effective relative to a self‐paced (SP) adaptation. Methods: A cost‐effectiveness analysis from a payer perspective was performed alongside a 2014‐2017 randomized behavioral weight loss trial among 248 active‐duty military personnel stationed at a US Air Force base in Texas. Incremental cost‐effectiveness ratios were calculated for weight loss, reductions in waist circumference, and quality‐adjusted life‐years (QALYs). Results: After 12 months, the CI adaptation cost more per participant compared with the SP adaptation (1, 081 vs. 120) but achieved greater weight loss (1.86 kg vs. 0.06 kg), greater reductions in waist circumference (1.85 cm vs. 0.48 cm), and more QALYs (0.871 vs. 0.856). The incremental cost‐effectiveness ratio for the CI adaptation relative to the SP adaptation was 61, 268 per additional QALY. At willingness‐to‐pay thresholds of 50, 000 and 100, 000 per QALY, the CI adaptation was 45% and 49% likely to be cost‐effective, respectively. Conclusions: The CI delivery of the Look AHEAD Intensive Lifestyle Intervention may offer a cost‐effective approach to tackle excess weight in the US military.